Emergence Corporate Financial Distressin Emerging Market: Empirical Evidence from Indonesia Stock Exchange(IDX) 2004-2008 - Koes Pranowo; Noer Azam Achsani; Adler H. Manurung; Nunung Nuryartono (Jurnal Manajemen & Agribisnis, 2011)
Financial recovery is the most difficult in financial management. Therefore, this is important to study how a company in financially-distress can survive to rise up to a healthy financial condition (emergence financial distress). The research consists of 200 non financial companies which are listed on Indonesia Stock Exchange (IDX) for the period of 2004-2008. This study focuses on management of working capital. How a company fulfill its current liabilities, and its sources in current assets which shall be cashed at the short term period. By using Multinomial logit, we analyzed the probability a financially-distress company rise up to emergence financial distress or stay of the status of financial distress and what are financial indicators affect to a company in the status of Non Financial Distress tend to Financial Distress. Thus, the important thing is to determine financial ratios which can be an indicator to determine of emergence financial distress. We find a positive relationship between Profit, efficiency and emergence financial distress and a negative relationship between leverage and emergence financial distress.   Keywords: Emergence Financial Distress, Indonesia Stock Exchange (IDX), Multinomial Logit JEL Classification Codes: G 3